Ethanol contributes to neurogenic pancreatitis by activation of TRPV1. Issue 2 (12th November 2013) - Vigna, Steven R.; Shahid, Rafiq A.; Liddle, Rodger A.
Abstract : Alcohol abuse is a major cause of pancreatitis in people, but the mechanism is unknown. It has been recently demonstrated that transient receptor potential vanilloid 1 (TRPV1) activation causes neurogenic inflammation and plays an important role in acute pancreatitis. Moreover, TRPV1 is activated by ethanol. We examined the direct effects of ethanol on acute pancreatitis. Acute inflammation of the pancreas was produced by injection of ethanol and palmitoleic acid (POA), a nonoxidative metabolite of ethanol, in wild‐type C57BL/6J mice and Trpv1 ‐knockout C57BL/6J mice. Inflammatory indexes were analyzed 24 h later. Injection of ethanol + POA produced acute pancreatitis indicated by significant increases in histopathological damage, serum amylase levels, and pancreatic MPO concentrations ( P <0.05–0.001). All parameters of pancreatitis were blocked by pretreatment with the TRPV1 antagonist drug AMG9810. In addition, ethanol + POA administration to Trpv1 knockout mice did not produce pancreatic inflammation. Treatment with vehicle, ethanol alone, or POA alone had no inflammatory effects. TRPV1 partially mediates inflammation induced by ethanol + POA in the mouse pancreas, consistent with the ability of ethanol to activate TRPV1. We propose that ethanol may contribute to alcohol‐induced pancreatitis by a neurogenic mechanism.—Vigna, S. R., Shahid, R. A., and Liddle, R. A. Ethanol contributes to neurogenic pancreatitis by activation of TRPV1. FASEB J. 28, 891–896 (2014). www.fasebj.org